2020
DOI: 10.5194/cp-16-117-2020
|View full text |Cite
|
Sign up to set email alerts
|

The end of the African humid period as seen by a transient comprehensive Earth system model simulation of the last 8000 years

Abstract: Abstract. Enhanced summer insolation during the early and mid-Holocene drove increased precipitation and widespread expansion of vegetation across the Sahara during the African humid period (AHP). While changes in atmospheric dynamics during this time have been a major focus of palaeoclimate modelling efforts, the transient nature of the shift back to the modern desert state at the end of this period is less well understood. Reconstructions reveal a spatially and temporally complex end of the AHP, with an earl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 92 publications
4
62
0
Order By: Relevance
“…It has been suggested that the greater magnitude of precipitation inferred from leaf wax proxies would require some rainfall in the winter season (Tierney et al, 2017). Some modeling studies do show marginally increased precipitation in the winter months (Dallmeyer et al, 2020; Tierney et al, 2017). However, as for the present, most precipitation in our mid‐Holocene simulations occurs only during the summer months with very little change to the precipitation pattern in winter months (Figures 1, S13, and S14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the greater magnitude of precipitation inferred from leaf wax proxies would require some rainfall in the winter season (Tierney et al, 2017). Some modeling studies do show marginally increased precipitation in the winter months (Dallmeyer et al, 2020; Tierney et al, 2017). However, as for the present, most precipitation in our mid‐Holocene simulations occurs only during the summer months with very little change to the precipitation pattern in winter months (Figures 1, S13, and S14).…”
Section: Resultsmentioning
confidence: 99%
“…An alternate approach to the question of Green Sahara utilizes dynamic vegetation models (DGVMs) wherein the distribution of vegetation is dynamically simulated and responds to the state of the climate (Claussen & Gayler, 1997;Rachmayani et al, 2015). Results from DGVMs have yielded varying levels of fidelity with proxy reconstructions (Braconnot et al, 2012(Braconnot et al, , 2019Claussen et al, 2017;Hopcroft et al, 2017) although recently Dallmeyer et al (2020) have obtained improved agreement with proxies using an updated Earth system model. DGVMs are not the subject of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Although the past decades have seen increasingly closer matches of simulated rainfall over the Sahel to that inferred from paleoclimate data, models that were tuned to match those data have continued to fall short in both precipitation amounts and latitudes of the rain belt. Coupled atmosphere‐ocean GCMs do better than those that use a slab ocean (e.g., Alder & Hostetler, 2015; Bosmans et al, 2012; Braconnot et al, 2000, 2002, 2007a, 2007b, 2019; Brown et al, 2008; Dallmeyer et al, 2018; Liu et al, 2017; Otto, Raddatz, Claussen, Brovkin, & Gayler, 2009; Otto, Raddatz, & Claussen, 2009; Shin et al, 2006). In particular, using an atmospheric GCM and 6‐ka insolation, Braconnot et al (2000) simulated the rain belt to lie ~2° north of that today, but with a coupled GCM, 3° north of it, if still short of some mid‐Holocene estimates that reach 5°.…”
Section: Mid‐holocene Sahel Precipitation Simulated Using Gcmsmentioning
confidence: 99%
“…To evaluate the δ 18 O calcite relationship to temperature through time, we compared the 100-year binned Waitomo δ 18 O ivc isotope master record to time-equivalent surface temperature series compiled from several transient Holocene climate model simulations (CCSM3-TracCE-21k [66]; EC-Bilt-Clio [67]; ECHO-G [68]; MPI-ESM1.2 [69]). Annually-resolved mean monthly temperature data from the grid cell closest to Waitomo (~38 • S and~175 • E) were obtained from each model; three-month averages (e.g., June-July-August, JJA; July-August-September, JAS; August-September-October, ASO; etc.)…”
Section: Time Series Coverage Limitations For Isotope Master Recordsmentioning
confidence: 99%